Prioritising crop wild relatives to enhance agricultural resilience in sub‐Saharan Africa under climate change. Issue 3 (30th November 2021) - Satori, David; Tovar, Carolina; Faruk, Aisyah; Hammond Hunt, Eleanor; Muller, Gemma; Cockel, Christopher; Kühn, Nicola; Leitch, Ilia J.; Lulekal, Ermias; Pereira, Laura; Ryan, Philippa; Willis, Katherine J.; et al.
Abstract : Social Impact Statement: Climate change is expected to disproportionately affect sub‐Saharan Africa in the next century, posing a threat to the livelihoods of smallholder farmers and deepening food insecurity. To adapt to this threat, more climate‐resilient crops need to be brought into the food system; these may be developed through breeding with crop wild relatives with key traits to cope with climate change. Here, we assess the level of open‐access trait documentation of crop wild relatives of 29 important crops, their resilience, how threatened they are in situ, how well they are preserved ex situ and we provide priorities for their conservation and use in breeding programmes. Summary: Climate change is projected to adversely affect smallholder agriculture in sub‐Saharan Africa (SSA) over the next century, with many areas becoming unsuitable for growing crops. Breeding programmes using crop wild relatives (CWRs) that are pre‐adapted to projected future climatic conditions may lead to more resilient crops, but their traits have not been screened across a large diversity of CWRs. Furthermore, many are threatened and require greater protection in situ and ex situ to prevent the loss of an important adaptive solution to climate change. A previous ecogeographical study found that 303 out of 836 CWRs of 29 major crops cultivated across SSA may represent priorities for future crop resilience. Here, we assessed the availability of trait information and compared traits between resilient and non‐resilient CWRs. Subsequently, we analysed the conservation status of CWRs in situ and ex situ to set new global priorities for protection. Our findings show that the traits of many CWRs are poorly described, but for those species with better coverage, key differences between resilient and non‐resilient CWRs were identified, including lower plant height amongst resilient CWRs of tree crops (arabica and robusta coffee, mango and cacao) and a higher likelihood of invasive CWRs to be resilient. We found that 14% and 36% of resilient CWRs are threatened in situ and absent from seed collections, respectively. Our study highlights CWR priorities for conservation based on resilience. A concerted international effort is recommended to conserve CWRs and improve agricultural resilience in a changing climate. Abstract : Climate change is expected to disproportionately affect sub‐Saharan Africa in the next century, posing a threat to the livelihoods of smallholder farmers and deepening food insecurity. To adapt to this threat, more climate‐resilient crops need to be brought into the food system; these may be developed through breeding with crop wild relatives with key traits to cope with climate change. Here, we assess the level of open‐access trait documentation of crop wild relatives of 29 important crops, their resilience, how threatened they are in situ, how well they are preserved ex situ and we provide priorities for their conservation and use in breeding programmes. Abstract : Il est prédit que le changement climatique affectera l'Afrique Sub‐Saharienne de manière disproportionnée d'ici à la fin du siècle, menaçant la subsistance des petits exploitants agricoles et renforçant l'insécurité alimentaire. L'apport de nouvelles cultures résistantes au climat futur représente une stratégie adaptative majeure; celles‐ci pouvant être développées lors de programmes de sélection à partir de l'usage d'espèces sauvages apparentées aux plantes cultivées possédant des traits fonctionnels associés à la résilience climatique. Dans cette étude, nous évaluons la disponibilité d'information de traits fonctionnels des parents sauvages de 29 cultures importantes, leur niveau de résilience au changement climatique, leur menace in situ, leur état de conservation ex situ, and nous proposons de nouvelles priorités pour leur préservation et usage. Abstract : El cambio climático afectará de manera desproporcionada a la región sub‐Sahariana de África en los siguientes cien años, poniendo en riesgo la subsistencia de los pequeños agricultores y agudizando el problema de la inseguridad alimentaria. Una estrategia adaptativa es el uso de cultivos fitomejorados con parientes silvestres que poseen rasgos funcionales que los hacen resilientes al cambio climático. En este trabajo evaluamos la disponibilidad de información de rasgos funcionales de parientes silvestres de 29 cultivos importantes, su nivel de resiliencia al cambio climático, que tan amenazados se encuentran in situ, que tan bien representados están en colecciones ex situ y proponemos prioridades para su conservación y uso en programas de fitomejoramiento.